On the Working Mechanisms of Solid‐State Double‐Layer‐Dielectric‐Based Organic Field‐Effect Transistors and Their Implication for Sensors - Pfattner, Raphael; Foudeh, Amir M.; Liong, Celine; Bettinson, Lance; Hinckley, Allison C.; Kong, Desheng; Bao, Zhenan (Advanced electronic materials, 2018)
Due to relatively low charge‐carrier mobilities in organic materials, high operational voltages often have to be applied and result in severe limitations. While it has been reported that elastic polymeric dielectrics, containing a very low ion concentration, are able to overcome this bottleneck, a systematic study on the working mechanisms and their implications for sensors is still missing. Due to the possibility to form a double‐layer capacitor while maintaining high insulating properties, such dielectrics enable stable low‐voltage devices, giving access to high current output and high on/off ratio even below 0.5 V. Field‐effect transistor devices are used to characterize this novel class of materials and to unravel their working mechanisms. To address their capability for sensors, a proof‐of‐concept experiment is performed, i.e., photoresponse is characterized and the field‐effect dependence is analyzed. Stable low‐voltage operation is a crucial issue, especially for biosensor applications which typically operate in physiological liquids and are limited by the small electrochemical window of water. Double‐layer dielectrics maintain high insulating properties, enable stable low‐voltage field‐effect transistors, giving access to high current output and high on/off ratio even below 0.5 V. High stability in aqueous media is shown as well as gate dependent photoresponse enabling tunable sensitivity. Stable low‐voltage operation is important for biosensors, which operate in physiological liquids and are limited by the small electrochemical window of water.